2022
DOI: 10.1002/hbm.25766
|View full text |Cite
|
Sign up to set email alerts
|

Altered processing of communication signals in the subcortical auditory sensory pathway in autism

Abstract: Autism spectrum disorder (ASD) is characterised by social communication difficulties.These difficulties have been mainly explained by cognitive, motivational, and emotional alterations in ASD. The communication difficulties could, however, also be associated with altered sensory processing of communication signals. Here, we assessed the functional integrity of auditory sensory pathway nuclei in ASD in three independent functional magnetic resonance imaging experiments. We focused on two aspects of auditory com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…This point is critical, because differences in task instruction in speech-innoise perception lead to the recruitment of different brain mechanism (Wild et al, 2012). Evidence that neural processing is altered when performing a speech recognition task comes from a previous study which included the same ASD and TD group participants as reported here (Schelinski et al, 2022). In that study, the TD group but not the ASD group showed enhanced responses in the right IC for speech-in-noise recognition as compared to speech recognition without noise.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This point is critical, because differences in task instruction in speech-innoise perception lead to the recruitment of different brain mechanism (Wild et al, 2012). Evidence that neural processing is altered when performing a speech recognition task comes from a previous study which included the same ASD and TD group participants as reported here (Schelinski et al, 2022). In that study, the TD group but not the ASD group showed enhanced responses in the right IC for speech-in-noise recognition as compared to speech recognition without noise.…”
Section: Discussionmentioning
confidence: 89%
“…We provide novel evidence that processes related to speech-innoise recognition in ASD are particularly altered in the left IFG. Only a few studies investigated the neural processing of speech-in-noise in ASD (Hernandez et al, 2020;Lin et al, 2021;Russo et al, 2009;Schelinski et al, 2022). Russo et al (2009) found altered brainstem responses in children with ASD as compared to typically developing children when passively listening to speech (i.e., syllables) when the speech signal was presented with and without additional noise (i.e., presented together with white noise).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations